An Off-Label Use of a Unibody Aortic Stent-Graft System for the Treatment of Infrarenal Abdominal Aortic Dissections - Joseph Faraj; Rebekah L. W. Tan; Bibombe P. Mwipatayi (Case Reports in Vascular Medicine)
Infrarenal abdominal aortic dissections (IAAD) are exceedingly rare, accounting for 1-4% of all aortic dissections. The evidence is scarce on how to best manage IAAD when they become symptomatic. Two main interventional approaches exist, open surgery and the endovascular approach. Conventional stent-graft systems make it difficult to treat nonaneurysmal aortic disease due to limb competition in a narrow distal aorta. Thus, we present a novel use of the Endologix Anatomical Fixation 2 (AFX2) Abdominal Aortic Aneurysm (AAA) endograft system for the treatment of four patients with IAAD. We also highlight an individual case study that was treated with an alternative endovascular approach and the complications that followed. This was to highlight and compare our successful experience with Endologix AFX2 AAA endograft system. There were multiple benefits for choosing this stent-graft; however the main advantage is its suitability in the narrow distal aorta. Our aim was to highlight an alternative endovascular approach for the successful treatment of a rare, challenging, and potentially fatal pathology.